COVID-19 Vaccine Booster Hesitancy (VBH) and Its Drivers in Algeria: National Cross-Sectional Survey-Based Study - Lounis, Mohamed; Bencherit, Djihad; Rais, Mohammed Amir; Riad, Abanoub (Vaccines, 2022)
Due to the emergence of various highly contagious variants of SARS-CoV-2, vaccine boosters were adopted as a complementary strategy in different countries. This strategy has, however, posed another challenge for the national authorities to convince their population to receive the booster after the first challenge of COVID-19 primer dose vaccines. This study was conducted to determine COVID-19 vaccine booster acceptance and its associated factors in the general population in Algeria. Using social media platforms, an online self-administered questionnaire was distributed between 28 January and 5 March 2022 for all Algerian citizens who received COVID-19 vaccines. Overall, 787 respondents were included in this study. Among them, 51.6%, 25%, and 23.8% accepted, rejected, or were hesitant about the COVID-19 vaccine booster, respectively. However, only 13.2% declared receiving the booster dose. Additionally, while 58.2% of the respondents declared being relieved after primer vaccination, 11.4% among them declared that they regretted being vaccinated. The most common reasons for acceptance were experts' recommendations (24.6%) and the belief that COVID-19 vaccine boosters were necessary and efficient, while rejection was mainly due to the belief that primer doses are sufficient (15.5%), or that vaccination in general is inefficient (8%). Males, older individuals, those with chronic comorbidities or a history of COVID-19 infection, non-healthcare workers, and those with low educational levels were associated with significantly higher odds for booster acceptance. Moreover, belief that booster doses were necessary and efficient, disagreeing with the notion that primer doses were not sufficient, experts' recommendations, and the desire to travel abroad were significantly associated with higher odds of COVID-19 vaccine booster acceptance.
Keywords: vaccine hesitancy; Algeria; vaccine acceptance; vaccine; vaccine booster; COVID-19